Calculation of Particle Emission Rates for Nucleon-Induced Reactions with non-Equidistance Spacing Model Dependence - Selman, Ahmed Abdul-Razzaq (Iraqi Journal of Physics, 2011)
Nuclear emission rates for nucleon-induced reactions are theoretically calculated based on the one-component exciton model that uses state density with non-Equidistance Spacing Model (non-ESM). Fair comparison is made from different state density values that assumed various degrees of approximation formulae, beside the zeroth-order formula corresponding to the ESM. Calculations were made for 96Mo nucleus subjected to (N,N) reaction at Emax=50 MeV. The results showed that the non-ESM treatment for the state density will significantly improve the emission rates calculated for various exciton configurations. Three terms might suffice a proper calculation, but the results kept changing even for ten terms. However, five terms is found to give the most appropriate conditions for calculation time and accuracy